Penerapan Konsep Restorative Justice Dalam Perkara Pidana Anak Di Wilayah Hukum Pengadilan Negeri Purwokerto - , Farida Tri Yugo Astuti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this research was to know the application of the restorative justice concept and obstacles encountered in the application of restorative justice concept in criminal cases of children in Purwokerto District Court jurisdiction where the implementation is an effort to support the provisions of article 45 the regulation No.3 in 1997, article 66 the regulation No. 39 in 1999 and article 64 the regulation No. 23 in 2002 so that children get their right of legal protection when conflict with the law. The research method used in this study is an empirical normative. This research is descriptive meaning of this study outline, illustrates and explain about the application of restorative justice concept in criminal cases of children in Purwokerto District Court jurisdiction. The Data collection instrumen in the form of direct interviews with the subjects related and literature studies which were then analyzed by qualitatively in order to obtain a clear answer and produce the correct data. The results of this study indicate that the rate of Investigation, the application of restorative justice be done investigating by using a form of discretionary authority possessed through diversion. At the attorney, restorative justice has not been applied because the prosecutor does not have discretionary authority as that possessed by the police because the authority of "termination of the prosecution in the public interest" in the application of the opportunity principle is based on the interests of the state and society, and not for personal gain. In addition, the authority is also only available to the General Attorney. At the district court, application of the concept of restorative justice to restore the balance of the criminal law has been applied to goals is to drop the action, but for serious crimes that are still subject to criminal sanctions, but did not rule out the possibility of restorative justice considered as ultimum remidium. Obstacles encountered in the application of restorative justice is the absence of regulation in the form of legislation that serve as guidelines for law enforcement leading to a lack of understanding of law enforcement officers and the public about the restorative justice process. In addition, it is very difficult to prevent children from punishment in retributive justice when children are very serious offense because not every case can be resolved in restorative justice.